2013
DOI: 10.1016/s0924-9338(13)77356-5
|View full text |Cite
|
Sign up to set email alerts
|

2763 – Psychiatric symptoms of internet game addiction in the child and adolescent psychiatric clinic

Abstract: Introduction:The prevalence of internet game use among children and adolescents has been increased in the recent years.Objectives:Internet addiction has been found to cause various psychiatric symptoms and psychological problems. Internet addiction has been found to cause various psychiatric symptoms and psychological problems.Aims:The aim of this study was to examine the association between problematic internet game use and psychiatric symptoms in a sample of the Child and Adolescent Psychiatric Clinic, Ulsan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Numerous studies have shown that internet addiction and depression often occur simultaneously, and internet addiction can increase the risk of depression, making it an important predictor of depression ( Oh et al, 2013 ; Ciarrochi et al, 2016 ). In recent years, with the development of mobile Internet technology and the emergence of smart phones, mobile phone addiction has become a new form of internet addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that internet addiction and depression often occur simultaneously, and internet addiction can increase the risk of depression, making it an important predictor of depression ( Oh et al, 2013 ; Ciarrochi et al, 2016 ). In recent years, with the development of mobile Internet technology and the emergence of smart phones, mobile phone addiction has become a new form of internet addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that addiction and depression often go hand in hand, and that addiction increases the risk of depression and is an important predictor of depression ( Oh et al, 2013 ). A 4-year follow-up study confirms that Internet addiction is a stable cause of depression ( Joseph et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%